Brain Abscess: A Comparison of Surgical Outcomes between Conventional Burr Hole Aspiration and Endoscope-Assisted Evacuation - Ahmed, Md Farhad; Rana, Sumon; Zahan, Kanij Fatema Ishrat; Munira, Shirazum; Islam, Mohammad Shafiqul; Haque, Monzurul; Pahwa, Bhavya; Aydin, Levent; Umana, Giuseppe Emmanuele; Chaurasia, Bipin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Brain abscesses are a major health problem with significant morbidity and mortality rates. The objective of this study was to compare the surgical efficacy of endoscope-assisted evacuation of a brain abscess with that of single burr hole aspiration in a tertiary health care center.Methods This single-center nonrandomized clinical study was conducted during the period from July 2020 to December 2021. Male and female patients younger than 30 years who presented with brain abscess were enrolled in this study. They were divided into two groups and treated with two different techniques: conventional burr hole aspiration group and endoscope-assisted evacuation group.Results Thirty patients were enrolled in this study. The mean age was 13.0 ± 6.3 years in the burr hole group and 13.1 ± 6.4 years in the endoscope-assisted group. There was ≥75.0% evacuation of brain abscess on postoperative day 1 in 13 (92.9%) patients in the endoscope-assisted group and in 5 (33.3%) patients in the burr hole group. The mortality rate was 6.7% in both groups. The mean residual volume on postoperative day 30 was 0.75 mL in the endoscope-assisted group and 1.75 mL in the burr hole aspiration group. No patients treated with endoscope-assisted evacuation required a repeat surgery, whereas five patients (33.3%) treated with the conventional burr hole method required a repeat surgery.Conclusions This study showed that the endoscope-assisted procedure has a better rate of abscess evacuation, lower residual risk, and less chance of repeat surgeries than the conventional burr hole procedure.
Keywords: brain abscess; endoscope; burr hole